Characterization, Antioxidant Activities, and Pancreatic Lipase Inhibitory Effect of Extract From the Edible Insect Polyrhachis vicina - Zhang, Zongqi; Chen, Sicong; Wei, Xunfan; Xiao, Jinhua; Huang, Dawei (Frontiers in Nutrition, 2022)
Oxidative stress and obesity are critical risk factors for metabolic syndrome. The consumption of functional food ingredients can a viable strategy to alleviate oxidative stress and obesity. In this study, the hydro-ethanolic extract of the edible insect Polyrhachis vicina was prepared and its phytochemical components were characterized. The total polyphenol contents, total flavonoid contents, antioxidant and pancreatic lipase (PL) inhibitory activities of the extract were determined in vitro. In total, 60 bioactive components were tentatively identified in the P. vicina extract. Polyphenols and fatty acids were further quantified using LC-MS and GC-MS, respectively. P. vicina extract possessed excellent antioxidant and PL inhibition acitivites. Salicylic acid, gallic acid, liquiritigenin, and naringenin, which were the major polyphenols in the P. vicina extract, interacted with PL through hydrogen bonding, hydrophilic or hydrophobic and pi-cation interactions. Thus, P. vicina extract can be used as a nutraceutical to alleviate oxidative stress-induced disease and manage obesity.